HUBUNGAN ANTARA PENDIDIKAN, PELATIHAN DAN LINGKUNGAN KERJA DENGAN PRODUKTIVITAS KERJA PEGAWAI DINAS TENAGA KERJA SEMARANG PROPINSI JAWA TENGAH - Heru Sri Wulan (Jurnal Ekonomi dan Bisnis Kontemporer, 2017)
Advances in technology production require the expertise and skills of human resources. Looking at the situations / circumstances that occur then one of the challenges faced by Indonesia today is how to utilize more human resources quantitatively and a potential supporter of the on-going national development. The issue of employment is closely related to some aspects such as labour utilization, quality, economic growth, the number and distribution of labour.. The population in this study were all employees within the Department of Manpower, Transmigration and Population of Central Java Province, located in Semarang, Jalan Pahlawan No. 16 Semarang with the number of employees 289 employees. In this study, a sample of 40 respondents drawn from various Secretariat / field and the various groups and various education with the hope to increase the accuracy and precision estimates. Data collection techniques are by means of interviews, questionnaires, documentation and literature. This study used two (2) analysis tools, namely analysis of qualitative and quantitative analysis.The results showed that training and work environment has a positive and significant impact on the productivity of work at the Department of Manpower, Transmigration and Population of Central Java Province.Keywords: Training, Environment, and Work Productivity